Improving Quality of Vehicle Tracking Systems in Hill Stations Using IEEE 802.16 Networks - Roop Singh Takur; E. Ramkumar (Institute of Advanced Engineering and Science, 2013)
IEEE 802.16 standard was designed to support the vehicle tracking system applications with quality of service(QOS). Tracking system is used for tracking the vehicles in hill stations with quality of service(QOS). With the help of subscriber station(SS) can track the vehicles. Subscriber station’s will provide signals to the mobiles and vehicles .In this paper, we propose a scheme, named vehicle tracking system, to track the vehicles without any interrupt in hill stations with quality of service(QOS). The idea of the proposed scheme is to track the vehicles in the roads of the hill stations which is coming in opposite direction and back of the vehicle. Analysis and simulations are used to evaluate the proposed scheme. Simulation and analysis results confirm that the proposed can track the vehicles with the help of subscriber station by given quality of service(QOS). Scheduling algorithms are proposed to improve the overall throughput. The simulation results show that our proposed algorithm improves the overall throughput by 40% in a steady network.DOI:http://dx.doi.org/10.11591/ijece.v3i1.2131